Penyuluhan Vaksin Covid-19 untuk Meningkatkan Kesadaran Mengikuti Program Vaksinasi Covid-19 - Oktianti, Dian; Angelica, Dita; Elvansi, M.; Abririn, Martina Lestiana (INDONESIAN JOURNAL OF COMMUNITY EMPOWERMENT (IJCE), 2022)
As a pandemic disease, Covid-19 has had a negative impact on people's lives and economy. In villages there is still frequent rejection of vaccination by the community, this is because people still believe that the circulating issues are not true and the lack of information on the right Covid-19 vaccine so that people do not dare to be vaccinated. Overall, Indonesia's population, on August 12, 2021, of the entire population, only 19% received dose 1 vaccination, and only 9.4% received complete vaccination. This is still very far from the number that has been targeted. This is due to the lack of information received by the public regarding the importance of the Covid-19 vaccination so that public awareness to follow is low. The PKK women in Mijen Village, Gedang Anak Village, are a small part of a community group that is expected to increase awareness to take part in the Covid-19 vaccination in their immediate environment. With the increased knowledge of mothers, they can choose reliable information so that people are not afraid to carry out the Covid-19 vaccination. This outreach activity uses the Zoom meeting media, due to reduce the risk of the spread of Covid-19. The enthusiasm of the PKK women in Mijen Village, Gedang Anak Village was very large, especially regarding information regarding the Covid-19 vaccination. The question that is often asked is that the Covid-19 vaccination will actually cause the person to be positive for Covid-19. In addition, it is about the use of eucalyptus oil which can be used as a treatment for Covid-19.ABSTRAKPandemi Covid-19 telah berdampak negatif terhadap kehidupan dan ekonomi masyarakat. Di desa-desa masih sering terjadi penolakan vaksinasi oleh masyarakat, hal ini dikarenakan masyarakat masih percaya dengan isu-isu yang beredar tidak benar serta kurangnya informasi vaksin Covid-19 yang tepat sehingga masyarakat tidak berani divaksin. Secara keseluruhan penduduk Indonesia, pada tanggal 12 Agustus 2021 dari seluruh populasinya baru sekitar 19% yang menerima vaksinasi dosis 1, dan baru 9,4% yang menerima vaksinasi lengkap 2 dosis. Hal ini masih sangat jauh dari jumlah yang telah ditargetkan. Hal ini disebabkan karena kurangnya informasi yang diterima masyarakat mengenai pentingnya vaksinasi Covid-19 sehingga kesadaran masyarakat untuk mengikuti menjadi rendah. Ibu-ibu PKK Desa Mijen Kelurahan Gedang Anak merupakan bagian kecil dari kelompok masyarakat yang diharapakan dapat meningkatkan kesadaran untuk mengikuti vaksinasi Covid-19 di lingkungan terdekatnya. Dengan meningkatnya pengetahuan ibu-ibu, maka dapat memilih informasi yang dapat dipercaya sehingga masyarakat tidak takut untuk melaksanakan vaksinasi Covid-19. Kegiatan penyuluhan ini menggunakan media Zoom meeting, dikarenakan untuk mengurangi resiko penyebaran Covid-19. Antusiasme ibu-ibu PKK Desa Mijen Kelurahan Gedang Anak sangat besar terutama mengenai informasi mengenai vaksinasi Covid-19. Pertanyaan yang sering ditanyakan adalah bahwa dengan vaksinasi Covid-19 justru akan menyebabkan orang tersebut positif terkena Covid-19. Selain itu adalah mengenai penggunaan minyak kayu putih yang dapat digunakan sebagai pengobatan Covid-19.